2018
DOI: 10.1007/s00268-018-4815-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Breast Cancer Multidisciplinary Patient Management: A Prospective Observational Evaluation of Team Clinical Decision‐Making

Abstract: BackgroundMultidisciplinary team (MDT)-driven cancer care is a mandatory UK national policy, widely used globally. However, few studies have examined how MDT members make decisions as a team. We report a single-centre prospective study on team working within breast cancer MDT.MethodsThis was a prospective observational study of 10 breast MDT meetings (MDM). Trained clinical observer scored quality of presented information and disciplinary contribution to case reviews in real time, using a validated tool, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 32 publications
(68 reference statements)
0
60
1
Order By: Relevance
“…Its broader impact on the literature surrounding MTB transformation has been demonstrated by the number of citations the development studies have accrued. MODe has been used by researchers: from use as a standalone assessment method in order to increase the understanding of team behaviours in MTB meetings, 11,13 to use in complex interventional studies alongside other performance metrics in order to assess the impact of interventions on aspects of team decision making. 10 This flexibility has undoubtedly increased the uptake of the tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its broader impact on the literature surrounding MTB transformation has been demonstrated by the number of citations the development studies have accrued. MODe has been used by researchers: from use as a standalone assessment method in order to increase the understanding of team behaviours in MTB meetings, 11,13 to use in complex interventional studies alongside other performance metrics in order to assess the impact of interventions on aspects of team decision making. 10 This flexibility has undoubtedly increased the uptake of the tool.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9] MODe has been used to assess decision-making processes across different tumour types in a number of different countries (Box 1). [7][8][9][10][11][12][13][14][15][16][17][18][19] MODe has been applied to show that the ability of an MTB to reach a clinical decision was positively associated with high-quality comprehensive and necessary information available at the point of decision-making (from case history, radiology, pathology), team contribution, 4,[9][10] and cases that are discussed at the beginning of meetings. [10][11] However, high-quality information and team contribution were positively correlated with the larger team size and longer case discussions.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no studies have evaluated and reported the responses of lung cancer MDT members to data presentation and feedback using a mixed‐methods approach. Several studies investigate aspects of MDT practice (from lung cancer and other streams), including processes, reporting to general practitioners, data characteristics, and timing of MDT discussion . The systematic review by Prades et al includes three papers that focus on aspects of lung cancer MDT care.…”
Section: Discussionmentioning
confidence: 99%
“…From studies involving other tumor streams, a UK study of comorbidity data collection by a single‐center colorectal cancer MDT showed a marked improvement with the introduction of routine ACE‐27 index calculation in surgical clinics prior to the MDT (increasing from 54% to 100% comorbidity data availability post‐intervention). A UK observational study of serial breast cancer MDT meetings in a single center identified higher quality biomedical information (history, radiology, and pathology) compared with patient‐related information (psychosocial, comorbidities, and patient views) as scored by the previously published MDT‐MODe assessment tool . Relatively few studies investigate multidisciplinary clinical care with qualitative methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation